Chronicling school principals’ experiences on school management in the context of COVID-19 stringency - Bonginkosi Hardy Mutongoza; Babawande Emmanuel Olawale; Busiswa Mzilikazi (Research in Social Sciences and Technology, 2021)
The COVID-19 pandemic experience has brought to the forefront the importance of leadership as institutions across the world are now trying to emerge from hibernation and rebuild broken academic practices. As such, this study sought to examine school principals’ experiences on school management in the context of COVID-19 stringency in four rural schools in the Eastern Cape Province of South Africa. Underpinned by a qualitative research approach, the study employed a case study design in which semi-structured interviews were used to collect data from four rural school principals who had been purposively sampled. Findings of the study revealed that in order to combat challenges associated with teaching and learning, school principals engaged among other things, in mobilization of resources, engendering a technological culture among teachers, ensuring effective delivery of content. We further ascertained that although hamstrung by resource inadequacies, school principals in rural schools promoted school safety by ensuring transparent and effective communication, striving for the provision of safe and adequate facilities, among other things. Finally, our study also revealed that rural school principals ensured clear and consistent communication with staff, provided psychosocial assistance to staff members, and adapted performance and workload expectations.